Dialektika Model Kepemimpinan Pendidikan Islam dari Berbagai Perspektif di Era Disruptif - Nurhidayah .; Sofyan Sauri; Faiz Karim Fatkhullah; Siti Honiah Mujiati (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
This article analyzes the dialectical problem of educational leadership models from various perspectives in the disruptive era. Leadership is one of the crucial issues in the management of education. The uneven quality of education at both the central and regional levels is a homework that still needs to be completed by the world of education. National Education Standards that have been formulated explicitly to be achieved as School or Madrasah thresholds are still stuck on administrative fulfillment only. The planning, implementation, evaluation and follow-up plans of the School Work Program do not yet reflect the needs of the school community. It takes an educational leader who has the appropriate qualifications and competencies to bring schools or madrasas to excel in this disruptive era. A complete understanding of the proper leadership model of educational leaders is one of the important knowledge for a leader to be able to improve the quality of the education of the institution he leads. Based on the background above, this paper presents various models of educational leadership from a theological perspective, a philosophical psychological perspective, sociology in order to improve the quality of educational leadership in the disruptive era.